Analisis faktor internal dan eksternal yang mempengaruhi holding period saham LQ45 - Ani Veridiana (MBR (Management and Business Review), 2020)
The research objective was to examine the effect of the bid-ask spread, market value, earnings per share, return on equity, inflation and the SBI interest rate on the holding period of shares. This study uses non-participant observation methods, namely by looking at data from the Indonesia Stock Exchange (IDX) and quantitative research types, there are 10 sample companies used in this study and using purposive sampling technique, in data collection is by documentation and variables used. in this study are the bid-ask spread, market value, earnings per share, return on equity, inflation and the SBI interest rate. There are variables that influence and there are two variables that do not influence, namely inflation and the SBI interest rate because the circulation values of the two variables are not good.